2022
DOI: 10.1096/fj.202101947r
|View full text |Cite|
|
Sign up to set email alerts
|

Lipidomic analysis revealed n‐3 polyunsaturated fatty acids suppressed choroidal thinning and myopia progression in mice

Abstract: Myopia is increasing worldwide and its preventable measure should urgently be pursued. N‐3 polyunsaturated fatty acids (PUFAs) have been reported to have various effects such as vasodilative and anti‐inflammatory, which myopia may be involved in. This study is to investigate the inhibitory effect of PUFAs on myopia progression. A lens‐induced myopia (LIM) model was prepared using C57B L6/J 3‐week‐old mice, which were equipped with a −30 diopter lens to the right eye. Chows containing two different ratios of n‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In addition, the effect of dietary supplementation of n-3 PUFAs on myopia, a condition that is increasing worldwide, was investigated in experiments conducted on mice, in particular on a model of lensinduced myopia (LIM). The results obtained showed that EPA and its metabolites are capable of inhibiting the choroidal thinning and the myopia progression [176].…”
Section: Curcumin and Quercetinmentioning
confidence: 96%
“…In addition, the effect of dietary supplementation of n-3 PUFAs on myopia, a condition that is increasing worldwide, was investigated in experiments conducted on mice, in particular on a model of lensinduced myopia (LIM). The results obtained showed that EPA and its metabolites are capable of inhibiting the choroidal thinning and the myopia progression [176].…”
Section: Curcumin and Quercetinmentioning
confidence: 96%
“…The flow rate and column temperature were set to 0.3 mL/min and 45°C, respectively. Data‐dependent MS/MS acquisition mode was applied as previously described 17 . Briefly, the temperature and ion spray voltage floating were set to 250°C(+)/300°C(−) and −5.5(+)/4.5(−) kV, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Data-dependent MS/MS acquisition mode was applied as previously described. 17 Briefly, the temperature and ion spray voltage floating were set to 250°C(+)/300°C(−) and −5.5(+)/4.5(−) kV, respectively. The accumulation times for MS1 and MS/MS were set to 250(+)/200(−) ms and 100(+)/70(−) ms, respectively, for scanning a mass range from m/z 70 to m/z 1250(+)/1750(−).…”
Section: Liquid Chromatography-mass Spectrometry-based Lipidomicsmentioning
confidence: 99%
“…In addition, the effect of dietary supplementation of n-3 PUFAs on myopia, a condition that is increasing worldwide, was investigated in experiments conducted on mice modelling lens-induced myopia (LIM). The results obtained showed that EPA and its metabolites are capable of inhibiting choroidal thinning and myopia progression [ 229 ].…”
Section: Role Of Antioxidants and Nutraceuticals In Maintaining Eye H...mentioning
confidence: 99%